Estudios de la biodegradación de cuatro tipos de bolsas oxo - biodegradables empleadas en la venta de productos, utilizando tierra compostable fresca, fresca más aireación y madura, simulando condiciones ambientales de humedad y temperatura del relleno sanitario ubicado en Quito. - Cadena Calvachi, Daniela Verónica (2014)
This work aboards the study of biodegradation of four types of oxo - biodegradable bags simulating the environmental conditions of temperature and humidity Landfill "El Inga" located in Pintag, belonging to the province of Pichincha, Quito. To star the study, research was conducted the shopping centers located in Quito to choose the most used plastic bags to sell their products, selected samples were subjected to a process of degradation through exposure to sunlight and environmental conditions in Quito for two months, then passed to a process of biodegradation placing for three months inside the biorreactor which simulated the design and conditions the land fill above mentioned. Throughout the experimentation the biodegradation process of the samples analyzed through methodologies for quantifying by weight, thickness (physical properties), stress (mechanical properties); Differential scanning calorimetry and infrared spectroscopy. At the end of the study it was observed that most of the samples were opaque; as to the results of the above analysis, a variation of similar weight and thickness was observed in the majority of samples, in the stress test results showed that the samples at the end of the experiment decreased their initial resistance and by analyzing the FT-IR spectrum it was found that in two of the samples studied the absorption band of carbonyl groups indicating began a process of degradation appeared.